A meta-analysis of risk taking and corporate performance - Phuong My Thi Pham; Binh Thanh Thi Dao (Cogent Business & Management, 2022)
Risk-taking is a topic that has been studied for many years in finance under the famous slogan in the financial industry "Higher risk, higher return". Nevertheless, empirical results have shown different scenarios. Using a sample of 56 researches with 406 studies covering millions of companies globally in the period from 2010 to 2020, this study applies a meta-analysis approach-a synthetic analysis approach to better understand the relationship between risk-taking and corporate return. Specifically, the studied risk-taking variables are: Leverage, Research and Development costs (R&D), and Firm Size; besides, the corporate return variables are Return on Assets (ROA), Return on Equity (ROE), Return on Sales (ROS), and Profit After Tax (PAT) standing for Accounting performance measures and Tobin's Q and Market to Book Value (MBV) standing for Market performance measures. Finally, the results have shown that Leverage, R&D, and Size have decent impacts on corporate returns, both Accounting performance and Market performance. Despite having some limitations, the study has provided critical insights into the literature review and established a big picture of the relationship between risk-taking and corporate return.
Keywords: 650; firm size; leverage; Meta-analysis; performance; R&D; risk-taking